Diffusion Along Dislocations Mitigates Self‐Limiting Na Diffusion in Crystalline Sn. Issue 52 (30th November 2020) - Byeon, Young‐Woon; Ahn, Jae‐Pyoung; Lee, Jae‐Chul
Abstract: The diffusion of carrier ions in alloying anodes often develops compressive stresses in front of the propagating interface, suppressing the carrier‐ion diffusion and limiting their full penetration into alloying anodes during battery cycles. This phenomenon, termed "self‐limiting diffusion (SLD)", reduces the rate performance of batteries and hinders the full usage of anode materials. However, SLD is mitigated in some systems where tensile residual stresses develop at the interface, causing them to manifest significantly improved rate performance and energy capacity. Here, a comparative study of LiSi and NaSn systems to elucidate how the differing diffusion kinetics displayed by the two systems can influence SLD behaviors and the rate performance of batteries is performed. Experiments show that the Na diffusion into soft Sn crystals induces tensile stresses near the interface, promoting the nucleation of high‐density dislocations. Thus‐formed dislocations facilitate Na diffusion at ultrafast rates by providing pathways for dislocation pipe diffusion and alleviate SLD, making crystalline Sn suitable for fast‐charging anode material. The outcomes of this study, while filling the knowledge gaps on the reasons for SLD, offer some guidelines for the appropriate choice of potential anode materials with superior rate performance and energy capacity suitable for future applications. Abstract : By performing in situ experiments, it is found that Na diffusion into soft crystalline Sn induces tensile stresses near the propagating interface, promoting the nucleation of high‐density dislocations. Thus‐formed dislocations provide pathways for dislocation pipe diffusion, which facilitates Na diffusion at ultrafast rates and alleviates self‐limiting diffusion behaviors.